Butterflies Behind Bars: Untold Stories of Incarcerated Homosexual Men - De Mar Bangeles (Journal of Social Science, 2023)
This study aimed to uncover the lived experiences of homosexual men behind bars; their coping mechanisms, as well as insights that can be learned from their incarceration. Qualitative research design by means of phenomenology was used with validated semi-structured interview guide as a tool in gathering the responses of the participants of this inquiry. The study employed an in-depth interview with nine participants incarcerated at the Bureau of Jail Management and Penology, Maa, Davao City, Philippines. The participants shared their primary experiences such as involvement with prohibited drugs, paying the price of one’s transgressions, dealing with painful realities behind bars, living with HIV/AIDS, longing for family, finding a little niche under the sun as a woman and relishing romantic relationships. The coping mechanisms of the participants included being actively involved and occupied, entertaining oneself with jovial activities, getting spiritual, being positive and accepting and getting a grip of oneself. The participants have also shared their insights as a result of their incarceration; live clean, stay away from drugs, alcohol and bad company, education is undoubtedly important, every action has a corresponding repercussion, there is something positive in every situation, and hope springs eternal.